Exploring national identity and modern art aesthetics, an investigation of the life, activities and artworks of Jalil Ziapour / Maryam Pournayebzadeh - Maryam , Pournayebzadeh (2019)
This research will investigate Jalil Ziapour; a pioneer Iranian modern artist.The study will also explore Iranian identity in his paintings as well as his artistic activities, anthropological studies, and changes during different phases of his life from 1920 to 1999 alongside, modernism and nationalist movements in Iran. Ziapour was a creative artist and an active academician during the different phases of his life. Since he was looking for inspiration and innovation through the artistic creations in Iran, many artists and scholars appreciated him as an important modern artist, who made advanced the art of painting in Iran. However, he is not explored well particularly when it comes to taking into account the different dimensions of his artistic life. In my research, I investigated Ziapour, taking into account various dimensions of his different artistic activities, including his biography, the social-political situation of his time, and his theory of modern art, his art writings and his anthropological studies. I studied how he integrated Iranian identity and modern art aesthetics in his paintings and I analyzed how his painting styles changed during different phases of his life.